A case report of Cholinergic syndrome an unusual complication of Neostigmine administration - Z Hussain Khan (Babol University of Medical Sciences, 2002)
Background and Objective: Cholinergic syndrome (Cholinergic crisis) is an extremely dangerous complication of anti-cholinesterase drugs such as neostigmine. Isolated forearm technique (IFT) with IV injection of neostigmine is used for the evaluation of awareness, which is a deliberate problem in narcotic based anesthesia. This method is used for evaluation of ischemia of the anterior spinal artery and weakness of upper extremity motor after operation of cervical spines. Case: The case was a 43-year-old woman with dislocated C1-C2 fracture who was candidated for cervical spines surgery. After IFT, induction of anesthesia and tracheal intubation (Muscarinic and nicotinic) Cholinergic symptoms of crisis were developed that the cause of this presentation was IFT with injection of neostigmine. Conclusion: Since, the evaluation of awareness is not so predictable by IFT procedure, it is recommended to use other modern techniques such as bispectral index, nerve stimulators and evoked potentials.